Penguatan Mitigasi Dan Edukasi Tanggap Darurat Tsunami Di Desa Batu Balak, Lampung Selatan - Rasimeng, Karyanto; Rasimeng, Syamsurijal; Maulida, Nanda Hanyfa; Mulyasari, Rahmi; Sinambela, Rudy Zefrianto (FT Universitas Lampung, 2024)
The tsunami is a worrisome natural disaster typically in coastal areas, including Batu Balak Village in South Lampung. The Selat Sunda tsunami on December 22 2018 hit the Batu Balak Village residents and resulted in material and non-material losses. The unpreparedness of the residents who experienced this incident is a reminder of the urgency of the need to increase community preparedness in facing this threat. On this basis, service activities were carried out to strengthen mitigation and education on tsunami emergency response in Batu Balak Village, South Lampung. This service activity aims to strengthen the mitigation process and educate the community regarding the potential for a tsunami disaster in the Batu Balak area. Another purpose is to increase public knowledge of disaster management. The methods used in this service are needs analysis, solution design, program assistance, and implementation. Based on the problem analysis, we carried out a workshop event on tsunami disaster mitigation, how to increase the social economy by utilizing geotourism, and made a recommendation map for tsunami evacuation routes and zones. The workshop event was attended by several residents and community leaders. The results obtained from this activity are an increased understanding of the people who present regarding the tsunami disaster, what mitigation processes need to be implemented when a disaster occurs, and how to handle the loss after the disaster.